2021
DOI: 10.1080/23288604.2021.1969721
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Adoption and Implementation of A Sugar-Sweetened Beverage Tax in South Africa: A Multiple Streams Approach

Abstract: This paper describes a case study of the adoption and implementation of the sugar-sweetened beverage tax in South Africa, termed the Health Promotion Levy. Qualitative data extraction and analysis of institutional documents, such as policy proposals and parliamentary debate records, stakeholder submissions to Parliament and media reports, were guided by the Kingdon Multiple Streams Theory as adapted to study agenda setting, policy adoption, and implementation. We present the following key findings: First, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Reduced consumption of sugar sweetened drinks has been recorded in countries like Mexico, the UK and South Africa which have implemented a sugar tax [ 60 , 61 , 62 ]. Fiscal measures are difficult to implement as they often face strong opposition from powerful industry [ 63 , 64 ]. This is true for Zambia where a sugar tax of 3% was adopted as opposed to the recommended 12% in part due to strong industry lobbying [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced consumption of sugar sweetened drinks has been recorded in countries like Mexico, the UK and South Africa which have implemented a sugar tax [ 60 , 61 , 62 ]. Fiscal measures are difficult to implement as they often face strong opposition from powerful industry [ 63 , 64 ]. This is true for Zambia where a sugar tax of 3% was adopted as opposed to the recommended 12% in part due to strong industry lobbying [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, advocacy coalitions and networks play a pivotal role to change power dynamics and resolving intractable policy stalemates as in the case of South Africa's ARV policy 91 92 and sugar tax policy. 49 This networked governance aligns with Focault's assertion that 'power is everywhere' and 'comes from everywhere' 124 and the idea that the government's role in global health has shifted from 'rowing the boat' to 'steering the boat'. 125 We also found that power can be used productively, including how opposition parties can initiate policy debates, form strategic pacts with ruling coalitions and capitalise on internal party solidarity to effect reforms.…”
Section: Bmj Global Healthmentioning
confidence: 68%
“…with public health benefits but with commercial costs and fiscal implications are subject to corporate resistance and under-prioritisation by governments particularly those aimed at controlling the production and use of tobacco, 46 47 alcohol 48 and sugar. 49 While these examples portray the distribution of benefits and costs as the basis of interest group competition that derails reforms, there are examples to the contrary. In Ghana, the framing of Anti-Microbial Resistance (AMR) not as a health problem but a multisectorial threat enabled stakeholder cohesion that helped to set and sustain the AMR agenda under the OneHealth Approach.…”
Section: Bmj Global Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of adopting the tax was complex. Civil society, academics and government actors supported the tax, buttressed by context-specific local evidence [ 16 ]. Industry and labour unions strongly opposed to tax, citing potential job losses and economic harms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%